EXAMINATION OF GUNSHOT RESIDUE DEPOSITED ON TARGETS WHEN SHELLS LOADED WITH POLEV SLUGS ARE FIRED FROM A 12 GAUGE SMOOTHBORE SHOTGUN - N. Grebenshchikova; O. Soldatova (Теория и практика судебной экспертизы, 2015)
The paper discusses the examination of patterns of gunshot residue deposition on targets after cartridges loaded with Polev slugs are fired from a 12 gauge smoothbore shotgun. We have established that firing shotgun shells loaded with Polev slugs from a distance further than close range causes penetration of target material with smaller and larger lead particles within a 100 mm radius around the entrance hole. When shots are fired from a distance of 5-to-25 m, the radius of GSR deposition, the number and size of lead particles increase.